"We Were Isolated and We Had to Do Whatever They Said": Violence and Coercion to Keep Adolescents Girls from Leaving the Sex Trade in Two U.S–Mexico Border Cities. Issue 4 (2nd October 2019) - Rocha Jiménez, Teresita; Salazar, Marissa; Boyce, Sabrina C.; Brouwer, Kimberly C.; Staines Orozco, Hugo; Silverman, Jay G.
ABSTRACT: Trafficked adolescent girls are at increased risk for sexual and physical abuse, HIV and STI (sexually transmitted infections) acquisition, mental health, and reproductive issues. While sex trafficking, in relation to adverse health outcomes, has been documented in prior research, this has been mainly explored once girls and women are already in the sex industry. However, less is known about the specific scenarios and contexts related to the recruitment and the different tools used to ensure women and girls remain in the sex trade. Qualitative in-depth interviews were conducted in Tijuana and Ciudad Juárez, Mexico among 16 current female sex workers who entered the sex industry under 18 years old. Participants reported being forced or coerced into the sex trade by romantic partners, friends, acquaintances, strangers, and/or family members. The main tactics traffickers employed were: violence and threats of violence, use of pregnancy and children, addiction and forced substance use. Certain cultural and social practices facilitate interactions between traffickers and adolescent girls (e.g., older men dating adolescent girls, normalization of violence) that later result in exploitative dynamics (e.g., sexual exploitation). Institutions and social mechanisms are key to maintain and facilitate some of these interactions. Consequences of sexual exploitation go beyond health consequences; they impact women's emotions, construction of sexuality, identity, and sexual rights among other elements of their lives. The results of this qualitative study may inform potential efforts to prevent coercion of adolescent girls into the sex trade and to assist those who have already been trafficked.